(untitled) (New York, 1986)
A multi-level course, supported by a broad range of supplementary material, which targets both accuracy and fluency in all four language skills.
Keywords: English language,English language,Tiếng anh; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Nói tiếng anh,Những vấn đề, bài tập